Attitydförändringar efter rovdjursangrepp : kunskap, attityd och ekonomi: en teststudie av en enkät - Melin, Tomas (SLU/Dept. of Animal Environment and Health (until 231231), 2018)
The effect of the predators in Sweden is substantial for many individuals. For others, they are pastime information contributed by media. Whether you are living with wild predators in your vicinity or not, an opinion is expected of you. Important things that shape opinions are the knowledge possessed, how personal the subject is and if it has an economic win or loss effect. This test study of an inquiry researches the change in opinion of cattle farmers after predator attacks. With questions of qualitative and quantitative form with an interpretation of hermeneutics with a good-reason-essay point of view, three main categories were focused on: Knowledge, attitude, and economics. Other studies have shown that gained knowledge may form and change opinions, and furthermore that television and the word of family and friends are the most regular forms of information sources for the Swedish inhabitants. While many variables are in effect when it comes to the attitudes kept towards predators, each variable has a different meaning depending on the individual. The attitudes seem stronger the more directly affected the holder of the opinion is by predator involvement. Some disbeliefs towards different oppositions seems to be in play. Economically, predators are a topic of some concern in Sweden, especially in interaction with game loss. Though economics is at loss when dealing with predators, it may not be as important as the affectional loss following the death of cattle. This is a very small test inquiry, therefore only indications of conclusions can be made. These indications are as follows: Knowledge is not taken from a sovereign source, the key factor for the attitude kept is first-hand experience and economics is not affecting opinion as simple as in money gained or money lost